Towards a patient-centered collaborative health care system model - Kotevska, Olivera; Vlahu-Gjorgievska, Elena; Trajkovik, Vladimir; Koceski, Saso (My University, 2012)
Recent advances in wireless sensor networks (WSN) technologies are enabling patient-centered, result oriented health care services, in the most cost-effective manner. Furthermore, technological advances are enabling a greater shift from institutional services to community-based services. The model of the collaborative health care system (COHESY) presented in this paper offers 24 hour monitoring of the condition of patients and the possibility of sending an emergency call for sudden deterioration of his medical condition. In addition, the system enables the patient (system user) to contact other people with similar condition and exchange their experience. This system improves the terms of home care treatment of the patient and also increases the medical capacity of the appropriate institutions. The result is significant reduction of the overall costs for patients and hospitals.
Keywords: Personal health care system, mobile application, social network